Phonological, morphosyntactic and semantic properties of reduplicated onomatopoeias in Karakalpak - Kdirbaeva Bakhitgul Keunimjaevna (Studia Humanitatis)
Reduplication, the repetition of a word or its part, is a linguistic mechanism found across many languages, including Karakalpak. This process is particularly common in onomatopoeic words. Karakalpak onomatopoeia exhibits various types of reduplication, including total, ablaut, echo and synonymous reduplication. These reduplicative patterns often convey the repetition, duration and continuity of sound events. Karakalpak onomatopoeia has some phonological features, including vowel and consonant frequencies and a preference for closed syllables. This paper examines phonological, morphosyntactic and semantic properties of reduplicated onomatopoeia in Karakalpak.